Pollution Is Colonialism - Liboiron, Max, 1980- (Book collections on Project MUSE., 2021)
"Max Liboiron models an anticolonial scientific practice aligned with Indigenous concepts of land, ethics, and relations to outline the entanglements of capitalism, colonialism, and environmental science."--